Transformative Impacts of AI and Wireless Communication in CSP Heliostat Control Systems - Quanwu Liu; Zengli Dai; Yuan Wei; Dongxiang Wang; Yu Xie (Energies)
In this review, the transformative impact of integrating artificial intelligence (AI) and wireless communication technologies into the heliostat control systems of concentrated solar power (CSP) plants are explored. Heliostat control systems are categorized based on wired and wireless implementations, and calibration methods are analyzed from traditional methods, auxiliary equipment, and AI in detail. The applications of artificial intelligence, machine learning, and deep learning techniques enhance the accuracy, control ability, and prediction performance of CSP heliostat control systems. At the same time, wireless communications play an important role in reducing costs, enhancing scalability, and enabling more flexible deployment. The synergistic impact of AI and wireless technologies improves the efficiency, reliability, and economic viability of heliostat systems, and shows great potential in global energy transition.